A crystalline bisindolylmaleimide with strong solid-state fluorescence of red color and its analogous cross-linked polymer without fluorescence. Issue 2 (17th February 2016) - Li, Ting-Ting; Jia, Yu-Hui; Huang, Mu-Hua; Wang, Yingxiong; Luo, Yunjun
Abstract: A crystalline bisindolylmaleimide (BIM)3 with strong fluorescence in the solid state was prepared and studied. Its analogous cross-linked polymer4 with the same BIMs fluorophore was designed and characterized. The investigation of the covalent bonding networking effect on the solid-state fluorescence was carried out by the comparison between3 and4 .